1997
DOI: 10.1093/intimm/9.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Role of thymic selection in the development of thymic lymphomas in TCR transgenic mice

Abstract: To investigate the role of antigen receptor-mediated interactions in lymphomagenesis we have analyzed the influence of alpha beta TCR-mediated selection on the development of spontaneous thymic lymphomas, which appear with a high (up to 50%) frequency in mice expressing a transgenic TCR specific for the male antigen (HY) in the context of H-2Db molecules. To this end we compared the kinetics and the incidence of thymic lymphomas developing in females and males with selecting (H-2b) and non-selecting (H-2k) MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The current work demonstrates that anti-CD3-mediated activation of endogenous TCR in human T-ALL has an antileukemic function. T-ALL often arises from immature T-cell precursors before the stage of negative selection ( 6,42 ). Consequently, contingent expression of a non-negatively selecting TCR will render T-ALL cells sensitive to TCR-activating apoptotic signals that mimic negative selection, as demonstrated here by anti-CD3 treatment in vitro and in vivo .…”
Section: Research Articlementioning
confidence: 84%
See 1 more Smart Citation
“…The current work demonstrates that anti-CD3-mediated activation of endogenous TCR in human T-ALL has an antileukemic function. T-ALL often arises from immature T-cell precursors before the stage of negative selection ( 6,42 ). Consequently, contingent expression of a non-negatively selecting TCR will render T-ALL cells sensitive to TCR-activating apoptotic signals that mimic negative selection, as demonstrated here by anti-CD3 treatment in vitro and in vivo .…”
Section: Research Articlementioning
confidence: 84%
“…Studies in T-ALL mouse models indicated a prooncogenic role for TCR signaling (39)(40)(41)(42). However, these data were based on transgenic TCR systems, which do not refl ect the expression levels and receptor diversity found among patients with T-ALL where TCR expression is heterogeneous or absent ( 6 ).…”
Section: Research Articlementioning
confidence: 99%
“…55 In this regard, TCR/ligand interactions may influence selection events in developing lymphomas. 56,57 To investigate the role of typical TCR/MHC in the development of Stat5-mediated T-ALL, we looked at the effect of Stat5b overexpression on ␤2m Ϫ/Ϫ or TCR␣ Ϫ/Ϫ backgrounds, settings in which normal TCR/MHC interactions do not occur. Stat5b TG ␤2m Ϫ/Ϫ and Stat5b TG TCR␣ Ϫ/Ϫ mice developed lymphomas, strongly suggesting that at least one of the primary events contributing to lymphoma formation in Stat5b TG mice must occur in the DN/DP population, prior to the point at which TCR/MHC interactions play a role in developmental decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 2-3% HY-TCR transgenic mice develop thymic lymphoma at 5 months of age, with increased tumor occurrence at older ages (28). At 3 to 5 months of age, some DGK␣ ϩ/ϩ ϩ/Ϫ -HY or DGK␣ ϩ/ϩ Ϫ/Ϫ -HY male but not female mice developed thymic lymphomas.…”
Section: Decreased Dgk␣ and Activities Promote Thymic Lymphomagenesismentioning
confidence: 99%